Implementation of Mathematics Learning For Early Childhood Through The Traditional Bekel Ball Game - Anisa Nurul Aini; RR. Deni Widjayatri; Fatihaturosyidah; Esya Anesty Mashudi; Lizza Suzanti; Budhi Tristyanto (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2022)
There are several things that need to be prepared to support children's development through the learning process, one of which is preparing media that can support aspects of their development. Most teachers only use an approach in the form of media images through worksheets without any modifications in the form of games. The purpose of this study is to describe the related Implementation of Mathematical Learning for Early Childhood 4-6 years Through the Traditional Game of Bekel Ball at PG-TK Islam Tirtayasa. This research uses a qualitative method. The research subjects were children aged 4-6 years old. With data collection techniques through an interview, observation, and documentation, classroom Action Research is an activity to improve learning practices to learning activities from problems that arise in learning situations. The results of the study are that there is an increase in the symbols for numbers 1-10 and knowing the shape of a circular geometric circle which if written in proportion is knowing the symbols for numbers 1-10 which is caused by stimulation of the child's brain for cognitive aspects through congklak media, as many children develop very well (BSB) 70% and children who develop as expected as much as 30% while children who know the geometry of circles with an unprecedented development rate as much as 80% and who develop as expected as much as 20%. This is also shown when the process of bekel ball games is done, namely the enthusiasm of children in playing and children are delighted when playing ball together with their friends so that the child does not feel that he is learning as well.